1993
DOI: 10.1007/bf00371591
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to cartilage collagens in relapsing polychondritis

Abstract: Relapsing polychondritis is a systemic disease associated with a destruction of cartilage in various parts of the body. Sera from six patients with relapsing polychondritis and one patient with microscopic polyarteritis nodosa as well as from six controls were analyzed by immunoblotting and ELISA. All patients had autoantibodies against native collagens II and IX. The serum from one patient showed a strong reaction with all three collagen chains of the high molecular weight fraction of collagen IX after denatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 20 publications
1
33
0
9
Order By: Relevance
“…They are generated against native and denatured collagen type II and collagen types IX and XI [15], which form the major extracellular scaffold in the cartilage. Studies [16,17] have shown that 33 % of patients with RP had circulating antibodies to type II collagen in the active phase of the disease and their titres also corresponded to disease activity.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…They are generated against native and denatured collagen type II and collagen types IX and XI [15], which form the major extracellular scaffold in the cartilage. Studies [16,17] have shown that 33 % of patients with RP had circulating antibodies to type II collagen in the active phase of the disease and their titres also corresponded to disease activity.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Cell-mediated immunity and anti-CII-specific Ab's have been observed in both RA and RP patients (12)(13)(14). In addition to CII, there is evidence of T cell responses and Ab's to type IX (CIX) and type XI (CXI) collagen in RP patients (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory parameters are not helpful in differential diagnosis, since in RPC there is no clear-cut or consistent laboratory abnormality. In some patients with RPC autoantibodies against collagen have been found, but these are obviously not restricted to this disease (Yang et al 1993).…”
Section: Discussionmentioning
confidence: 99%